Role of human antigen-specific T cells in tolerance and IgE-mediated allergic reactions to food - López-Fandiño, Rosina (Frontiers in Immunology, 2025)
Allergen-specific CD4+ T cells play a pivotal role in the pathophysiology of food allergy and in the induction of tolerance during desensitization. However, their study remains challenging due to the considerable heterogeneity in the frequency and phenotype of food allergy-specific Th2 cells in allergic individuals, together with an extremely low abundance of T cells specific to a given allergen. Furthermore, a major limitation of human studies is their reliance on peripheral blood sampling, whereas higher frequencies of allergen-specific cells may reside in intestinal tissues directly implicated in the allergic response. Among the most targeted approaches to quantify and characterize these cells stand MHC class II tetramers and activation-based detection methods. These techniques have identified pathogenic Th2 cell subpopulations in allergic individuals, that are absent in non-allergic subjects and differentiate patients with diverse degrees of clinical reactivity. These cells, crucial in driving immune responses and mediating immunological memory, exhibit distinct phenotypic and functional properties compared to conventional Th2 cells. However, there is no conclusive evidence supporting a definitive role for allergen-specific regulatory T (Treg) cells in food allergy, natural tolerance, or desensitization following immunotherapy. Moreover, pathogenic Th2 and Treg cells may differ in their allergen specificity, potentially due to priming by distinct sets of food-derived antigens. A deeper understanding of the characteristics and roles of specific pathogenic Th2 and Treg cell populations in food allergy could pave the way for novel preventive and therapeutic strategies for this disease.